Food, fermentation and micro-organisms - Bamforth, Charles W.; Cook, David J. (UK Willey Blackwell, 2019)
-"Covers all major uses of fermentation in the global food and beverage industries. -Contains practical information on the processing of fermented food and beverage products. -Author is an internationally renowned authority on the subject. -Second edition chapters significantly updated and expanded, particularly those on non-beverage products. Market description Food scientists, technologists and microbiologists in the food industry and in academia"--
Includes bibliographical references and index.
Keywords: Fermented foods; Fermentation; Yeast; Microorganisms